Investment Valuation of Energy Efficiency Measures within Mining Companies - SERGEEV, Igor; MINEEVA, Anna; LEBEDEVA, Olesia (Journal of Advanced Research in Law and Economics; Vol 8 No 2 (2017): Volume VII, Issue 2(24), Spring 2017, 2017)
The research is aimed at revealing and classifying the multiple benefits that mining companies obtain implementing energy efficiency measures. The relevance of the subject is justified with two substantial issues. Firstly, mining companies are seeking energy cost reduction to achieve competitive advantages. Secondly, it is important to reveal essential benefits that can improve investment attractiveness of energy efficiency measures from business point of view. Within the study, multiple effects are considered, which are relevant to corporate level of gold mining companies operating in the Russian business environment. The research framework implied a case study. The process of primary and secondary data collection was performed through in-depth expert interviews with company’s management, analysis of relevant Russian tax legislation, and some statistical data. The revealed effects were classified into measurable and non-measurable in order to show explicitly which effects might be directly included in investment analysis. The measurable effects include energy savings, increase in output, tax benefits, decrease in environmental compliance payments. These effects are essential from business point of view since they improve project’s financial indicators. The tax benefits, which are applicable to the Russian mining companies implementing energy efficiency measures, were evaluated.